PWE-407 Scottish surgical boot camp: an induction to a community of practice. (22nd June 2015) - Cleland, J; Gale, M; Nicol, L; Hogg, M; Watson, A; Walker, K
Abstract : Introduction: A reduction in hours of "apprentice style" training, has led to increased interest in alternative pedagogic paradigms. Intensive "Boot Camps" have been found to accelerate the acquisition of key surgical skills. 1 A 4 day residential Scottish Surgical Boot Camp in the Inverness Clinical Skills Centre is now adopted by 2 Royal Colleges and recommended for 1 st year Core Surgical Trainees in Scotland. It is simulation-rich and includes technical and non-technical skills, e.g. wet labs, simulated ward rounds, etc. Evaluation of other Boot Camp models have been from the quantitative perspective of efficacy of training, 2 usually limited to Kirkpatrick levels 1 and 2. We take a qualitative perspective to explore the development and delivery of this Boot Camp. Method: Grounded in social constructivism and consistent with the theoretical lens of cultural-historical activity theory, 3 we used a rapid ethnographic approach 4 involving observations, semi-structured formal interviews with faculty and field interviews with students and faculty to understand the relationships and processes of the SSBC. Results: Kirkpatrick level one feedback was positive. Further, our empirical data showed the important factors shaping the design, aims, objectives, development and positioning of SSBC within national training programmes, and a surgical community of practice. Interviews with faculty provided a picture of how the content of SSBC had changed over time in response to the trainee needs, curricular changes and growing faculty expertise. Within the SSBC, there were clear rules and expectations, division of labour, and social and skills-focused learning objectives. Conclusion: This theory-grounded case study gives a unique insight into the complexity of interacting influences shaping a Boot Camp, which we believe enables a better description and understanding of the SSBC. Further data illustrating the usefulness of CHAT as a means of developing and evaluating this educational activity will be presented on the day. Disclosure of interest: None Declared. References: Cohen ER, Barsuk JH, Moazed F, Caprio T, Didwania A, McGaghie WC. Making July Safer: Simulation-Based Mastery Learning During Intern Boot Camp. Acad Med. 2013;88:233–239 Parent RJ, Plerhoples TA, Long EE, et al . Early, intermediate, and late effects of a surgical skills "Boot Camp" on an objective structured assessment of technical skills: a randomized controlled study. J Am Coll Surg. 2010;210: 984–989 Engestrom Y, Miettinen R, Punamaki R. Activity Theory and Individual and Social Transformation. Perspectives on Activity Theory. Cambridge: Cambridge University Press 1999 Savage J. Ethnography and healthcare. BMJ 2000;321:1400